The influence of micro-elements on the yield and composition of Ladino clover in the George area - Starke, J. J.(Jacobus Joubert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1955.